2022
DOI: 10.1177/1420326x221134981
|View full text |Cite
|
Sign up to set email alerts
|

The building plan automatic design optimization based on CFD numerical intelligent simulation

Abstract: To apply the thermal comfort to the optimization of building layout, a variable design method based on Kmeans clustering is proposed. The evaluation was based on numerical simulation, genetic algorithm and universal thermal climate index (UTCI) to implement the building layout optimization on Matlab. Finally, the building layouts with centralized type, decentralized type and edge flow type water configuration were optimized, respectively. The results show that after the optimization, a reduction of 0.1∼0.6°C o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Studies have been carried out on energetic optimization-calculation range from those on passive design to those on radiant cooling; however, they do not optimize the geometry from a design perspective. [43][44][45][46] This study was aimed at extending the TEAM-TComBE method reported by Yamamoto et al 37 to develop a set of guidelines for use in the thermal design process of buildings. This study compared the results of accuracy verification and computational-load reduction to accumulate fundamental knowledge for a basic design using the TEAM-TComBE method.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have been carried out on energetic optimization-calculation range from those on passive design to those on radiant cooling; however, they do not optimize the geometry from a design perspective. [43][44][45][46] This study was aimed at extending the TEAM-TComBE method reported by Yamamoto et al 37 to develop a set of guidelines for use in the thermal design process of buildings. This study compared the results of accuracy verification and computational-load reduction to accumulate fundamental knowledge for a basic design using the TEAM-TComBE method.…”
Section: Introductionmentioning
confidence: 99%
“…RL. RL is a novel branch of ML that utilizes a closed-loop feedback control framework [21,54,38]. It represents a novel approach to automatically discovering the optimal control strategy [45,69].…”
mentioning
confidence: 99%